Immunization with the lipoprotein FtsB stimulates protective immunity against Streptococcus pyogenes infection in mice - He, Li-Yuan; Yu, You-Bo; Liu, Ying; Le, Yao-Jin; Li, Sha; Yang, Xiao-Yan (Frontiers in Microbiology, 2022)
Streptococcus pyogenes is one of the main pathogenic bacteria that causes disease in humans. It is reported that over 18 million cases of S. pyogenes disease occurred in the world, and more than 500,000 deaths occur annually worldwide. An effective vaccine is widely regarded as the most reliable way to control and prevent streptococcal infections. However, there is currently no approved vaccine for S. pyogenes. In this study, we evaluated the potential of lipoprotein FtsB as a new vaccine candidate to prevent S. pyogenes infection. Mice vaccinated with purified FtsB protein elicited high titres of IgG, IgG1 and IgG2a antibodies in mouse serum. Vaccinated with FtsB can reduce bacterial systemic dissemination in the blood, heart, and spleen and reduce organ damage in the mouse bacteraemia model. In addition, active immunization with FtsB protected against streptococcal abscess formation. Furthermore, immunization with FtsB was efficient in inducing a mixed cellular immune response and promoting the maturation of dendritic cells in mice. These findings demonstrated that lipoprotein FtsB may serve as a candidate vaccine for the prevention of S. pyogenes infection.